2022
DOI: 10.1021/acs.jpclett.1c03719
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Prediction of Mixed-Valence Layered Halide Perovskites Cs4M(IV)M(II)2X12 (M = Ge, Sn; X = Cl, Br)

Abstract: Charge-ordered compounds (i.e., Cu+/Cu2+, Au+/Au3+, In+/In3+, Tl+/Tl3+, Sb3+/Sb5+, and Bi3+/Bi5+) have been widely explored because of their unique physical properties. Here, a new class of ⟨111⟩-oriented mixed-valence layered halide perovskites Cs4M­(IV)­M­(II)2X12 (M = Ge, Sn; X = Cl, Br) with C2/m, R-3m, and I41/amd space groups was predicted by first-principles calculations. Based on the decomposition enthalpy, the phonon spectrum, and the mechanical stability criteria, we found that Cs4GeGe2Cl12 (C2/m and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…[4,5] Although there are various lead substitutes (Sn, Ge, etc.) available, [6] these substitutions obstruct band alignment as the B-cation and halide play a vital role in band edge creation in the ABX 3 structure which impacts optoelectronic characteristics. Many researchers have been working to develop lead-free [7,8] and environmentally acceptable perovskites for green-energy photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Although there are various lead substitutes (Sn, Ge, etc.) available, [6] these substitutions obstruct band alignment as the B-cation and halide play a vital role in band edge creation in the ABX 3 structure which impacts optoelectronic characteristics. Many researchers have been working to develop lead-free [7,8] and environmentally acceptable perovskites for green-energy photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…have been extensively investigated. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Han and colleagues reported the colloidal synthesis of air-stable Cu(I) − Sb-based DP Cs 2 CuSbCl 6 nanocrystals (NCs) with a bandgap of 1.66 eV, which showed that these NCs would have great potential to be used as a light-absorbing material. [34] The stable Cs 4 CuSb 2 Cl 12 layered DP powders and NCs with a direct small bandgap and superior optoelectronic properties were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials are widely used in the field of optoelectronics, and many perovskites have excellent performance in the field of thermoelectricity. [5][6][7][8][9][10][11][12][13] Compared with simple perovskite, double perovskite has the advantages of nontoxicity and structural stability, and it is an excellent potential TE because of its rich elemental variety and low cost. Among them, halide based double perovskites are suggested new type of TE materials due to good electrical transport and low phonon transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite materials are widely used in the field of optoelectronics, and many perovskites have excellent performance in the field of thermoelectricity [5–13] . Compared with simple perovskite, double perovskite has the advantages of non‐toxicity and structural stability, and it is an excellent potential TE because of its rich elemental variety and low cost.…”
Section: Introductionmentioning
confidence: 99%